Pengaruh Pembayaran Utang Pasca IPO Terhadap Pertumbuhan Perusahaan - Ana Inelia; Nurzi Sebrina (Universitas Negeri Padang, 2019)
This study to examine the effect of post-IPO debt payments on firm growth. Research is a causative research, the population are the companies which listed on the Indonesia Stock Exchange in 2013-2017, there are 64 companies as research samples that obtained from www.idx.co.id, method used is multiple linear regression analysis. The results showed that DER has a significant effect, which means that a high level of leverage can be proven to increase the motivation of companies to use IPO funds to pay debts and interest spread has no significant effect. It means that a high level of interest spread cannot explain firm motivation using IPO funds to pay down debt. high retiring has no significant effect, which means that a high debt payments cannot prove an increase in firm growth and the low retiring has no significant effect, meaning that low debt payments cannot explain the increase in firm growth. POSTIPO which has no significant effect, that means that post-IPO conditions cannot prove a better long-term operating performance and POSTIPO * HR has no significant effect, which means the reaction conditions post-IPO with a high level of debt payments cannot prove that long-term operating performance length is better.